PENGARUH JUMLAH PRODUKSI, HARGA KAKAO INTERNASIONAL DAN NILAI TUKAR KURS TERHADAP EKSPOR KAKAO INDONESIA KE PASAR INTERNASIONAL - Nugraha, Dewa Andika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p02, 2022)
Cocoa is one of the important trading commodities in the world to generate foreign exchange. Indonesia's cocoa export activities each year always fluctuate so that the foreign exchange to be achieved is not in accordance with the set targets. The purpose of this study was to analyze empirical evidence of the effect of total production, international cocoa prices and exchange rates on Indonesian cocoa exports. This study uses secondary data with non-behavioral observation data collection methods. The analysis technique used is panel data regression analysis with a total sample of 55 observations. Based on the results of the study, it was found that the amount of production, international cocoa prices and the exchange rate simultaneously had a significant effect on Indonesian cocoa exports. The results of his study also show that the amount of production and international cocoa prices partially positive and significant effect on cocoa exports while the exchange rate has no positive and partially significant effect on Indonesian cocoa exports.